A lateral flow biosensor based on gold nanoparticles detects four hemorrhagic fever viruses. Issue 46 (13th November 2020) - Zhao, Jin; Fang, Shuting; Liu, Yujie; Zeng, Lingwen; He, Zhixu
Abstract : The pathogen of viral hemorrhagic fever (VHF), which is harmful to human health, is a hemorrhagic fever virus. Abstract : The pathogen of viral hemorrhagic fever (VHF), which is harmful to human health, is a hemorrhagic fever virus. Clinicians have long needed convenient and sensitive point-of-care rapid diagnostic tests (RDTs) for hemorrhagic fever viruses. Commonly used methods for pathogen detection rely on conventional culture-based tests, antibody-based assays and polymerase chain reaction (PCR)-based techniques. However, these methods are costly, laborious and time-consuming. Herein, we present a simple and sensitive biosensor for the rapid detection of hemorrhagic fever viruses. For this assay, we develop lateral flow biosensors (LFBs) based on magnetic beads and nicking enzyme-assisted isothermal strand-displacement amplification (SDA) for the detection of hemorrhagic fever viruses. The detection limit of this assay is 10 fM.